Contribution aux recherches sur le jardin moderne en Espagne - Rémy Bercovitz (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Translated into French for the first time, the four texts presented here are those of one of the most important landscape architects and garden designers in Spain at the beginning of the twentieth century. These texts have been chosen because they are representative of Javier de Winthuysen’s thinking on landscape. The critical edition of these texts is intended to provide research material for a rapidly developing field: the history of garden design in the early twentieth century and its relationship with modernity.